Pure spin squeezing of h-BN spins coupled to superconducting resonator - Qiao, Yi-Fan (2023)
The negatively charged boron vacancy (VB-) spin defect in two-dimensional (2D) hexagonal boron nitride (h-BN) has attracted much attention for potential applications in quantum photonics recently. Its inherent van der Waals force mechanism guarantees convenient heterostructures for quantum sensing. By virtue of such materials, researchers not only can fabricate enough thin spin film naturally close to the sensing target but also can prepare an almost perfect spin ensemble with a uniform orientation. We here propose a setup with an ensemble of VB- spins strongly coupled to the superconducting coplanar waveguide resonator through the magnetic-dipolar interaction. The collective coupling strength is predicted to be G/2π∼15 MHz, which corresponds to the strong coupling region. This collective spin-photon interaction can mimic the one-axis twisting Lipkin-Meshkov-Glick model effectively and therefore guarantee the dynamic generation of the spin-squeezed state. In addition, we show the influence of inhomogeneous coupling caused by sample thickness on squeezing, which proves the validity of the homogeneity assumption in our scheme. This attempt not only explores the possibility and superiority of 2D VB- spins but also opens another avenue for quantum hybridization.